Rat Liver Energetic State Under Short-Term Hypothermic Storage - Tkacheva, E. N.; Semenchenko, O. A.; Somov, A. Yu.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2007)
The effect of pretreatment of rats with fetal tissue cytosol on mitochondrial functional state and ATP content in isolated liver under short-term hypothermic storage has been studied. Animal pretreatment with fetal tissue cytosol was shown to result in a statistically significant increase in ATP content in an isolated liver following 1 hr of organ hypothermic storage as well as in succinatedependent respiration rate rise in V3 and V4 state according to Chance. Respiration rate in malate and glutamate presence did not differ from the control values.